Ganges Coastal Zone Platform Workshop Report - International Rice Research Institute (International Rice Research Institute, 2017)
A two-day meeting was held in Bangkok with the goal of establishing a platform for improved sharing, networking, complementarities and synergies across the many R4D projects on production systems (agriculture, aquaculture) and water management in the Ganges coastal zone. The focus of the workshop was the Bangladeshi coastal zone. The 36 participants included representatives of NARS, international R4D organization, donors and NGOs.